The magnitude of neonatal near miss and associated factors among live births in public hospitals of Jimma Zone, Southwest Ethiopia, 2020: A facility-based cross-sectional study. - Merertu Wondimu; Fikadu Balcha; Girma Bacha; Aklilu Habte (PLoS ONE, 2021)
Background Neonates with severe complications at birth or during the neonatal period who nearly died but survived constitute neonatal near miss (NNM) cases. Identifying NNM cases and correcting contributing factors are of the utmost importance to get relevant controls for neonatal deaths. However, limited studies are assessing the prevalence of NNM and associated factors with NNM cases in Ethiopia. So, this study is aimed at assessing the magnitude of neonatal near miss and associated factors among live births in public hospitals of Jimma zone, southwest Ethiopia, 2020. Methods A facility-based cross-sectional study was conducted among 260 neonates from April 1-30 / 2020. Face to face interviewer-administered structured questionnaire was used to collect data from the mothers and a standard checklist was used for their neonates. The data was encoded and entered into Epi-Data version 4.2 and exported to SPSS version 23 for analysis. Independent variables with marginal associations (p-value <0.25) in the bivariable analysis were eligible for multivariable logistic regression analysis to detect an association with outcome variables. Finally, adjusted odds ratios (AOR) with 95% CI were used to estimate the strength of associations, and statistical significance was declared at a p-value < 0.05. Result The magnitude of NNM was 26.7% with [95%CI: 21.6-32.5]. Hypertension during pregnancy [AOR: 3.4; 95%CI: 1.32-8.88], mode of delivery [AOR: 3.32; 95%CI: 1.48-7.45], Obstructed labor [AOR: 2.95; 95%CI: 1.32-6.45] and non-vertex fetal presentation during delivery [AOR: 4.61; 95%CI: 2.16-9.84] were identified as significantly predictors of NNM. Conclusion and recommendation Over a quarter of the neonates were with NNM cases, which is relatively higher than the report of studies done in other countries. Hypertension during pregnancy, cesarean delivery, prolonged labor, and non-vertex fetal presentation were all found to increase the likelihood of NNM. Therefore, concerted efforts are needed from local health planners and health care providers to improve maternal health care services especially in early identification of the complications and taking appropriate management.